PENGARUH PARTISIPASI MASYARAKAT, KOMPETENSI SUMBER DAYA MANUSIA DAN PENGAWASAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Watu, Dionisia; Londa, Yulita; Sayang, Sabulon (Jurnal Riset Ilmu Akuntansi, 2023)
The aims of this research are 1. To find out the effect of community participation on the accountability of managing village funds in Golewa District, Ngada Regency. 2. To determine the effect of human resource competence on the accountability of managing village funds in Golewa District, Ngada Regency. 3. To find out the effect of supervision on the accountability of managing village funds in Golewa District, Ngada Regency. This type of research uses causality research, the research was conducted in villages throughout Golewa District, Ngada Regency, the research data obtained will be analyzed with the help of the SPSS (Statistical Package for the Social Sciences) software application. Based on the results of the study, data was obtained that: The results of testing the community participation variable showed a regression coefficient value of 0.304. The tcount value of the community participation variable > ttable (2.047 > 2.02439) and a significant level of 0.048 <0.05. The results of testing the human resource competency variable show a regression coefficient value of 0.277. The tcount value of the human resource competence variable > ttable (2.184> 2.02439) and a significant level of 0.035 <0.05. The results of testing the community participation variable showed a regression coefficient value of 0.743. The tcount value of the community participation variable > ttable (3.262> 2.02439) and a significant level of 0.002 <0.05.